Analisis Sistem Informasi CRM Untuk Meningkatkan Pelayanan dengan Pendekatan SDLC (Studi Kasus: UMKM â€œSAKTIâ€) - STT, Latjuba Sofyana; Putera, Andi Rahman (LPPM Universitas Merdeka Madiun, 2019)
The development of information technology is endless. Every day there is something new that we can find outside. Will affect many sectors. One of the fastest growing is UMKM. Screen printing and convection is one of the UMKM that produces and sells plain shirts and screen printing. To improve its services, screen printing and convection information systems need to be developed so that the service is more optimal, effective and efficient. Customer Relationship Management (CRM) is a core business strategy that can support, obtain and retain customers. Based on the results of the needs analysis and system analysis of the company that can be known about the CRM modules needed for the system are Customer Service and Support (CSS) and Entreprise Marketing Automation (EMA).